SIG Pemetaan dan Hasil Panen Perkebunan Kopi Kabupaten Kendal Tahun 2017 – 2019 - Risma Bidayatul Hidayah (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This research focuses on the Geographic Information System (GIS) which is used to analyze the mapping and harvest results of coffee plantations in Kendal Regency during the period 2017 to 2019. The hope is that this system will provide information about identifying zones that have high potential for coffee production, as well as environmental factors that influence coffee harvests in Kendal Regency. This research provides a contribution that can be used to improve planning in the future development of coffee plantations, including increasing productivity and farmer welfare. The research methodology involves collecting spatial and non-spatial data then continuing with map design using QGIS software.